2018
DOI: 10.1136/bmjopen-2017-019894
|View full text |Cite
|
Sign up to set email alerts
|

Multiple types of human papillomavirus infection and anal precancerous lesions in HIV-infected men in Taiwan: a cross-sectional study

Abstract: ObjectivesThis study aimed to assess the relationship between infection with multiple human papillomavirus (HPV) types and abnormal anal cytology in HIV-infected men.DesignAn observational, cross-sectional study.SettingA regional referral hospital in Taiwan.ParticipantsIn total, 714 HIV-infected men were enrolled between March 2011 and June 2016. Thin preparation anal Pap smears were interpreted according to the 2001 Bethesda System. Thirty-seven types of HPV were detected by reverse line blotting, including 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 36 publications
5
11
0
2
Order By: Relevance
“…All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV‐infected patient who was positive for possibly carcinogenic HPV‐53. These results are consistent with those reported in a recent French multicenter study of HIV‐infected MSM and in a cross‐sectional study of HIV‐infected men recruited in Taiwan …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…All individuals with an HSIL harbored an HR HPV infection with the exception of 1 HIV‐infected patient who was positive for possibly carcinogenic HPV‐53. These results are consistent with those reported in a recent French multicenter study of HIV‐infected MSM and in a cross‐sectional study of HIV‐infected men recruited in Taiwan …”
Section: Discussionsupporting
confidence: 92%
“…The odds of having an ASCUS 1 report increased by 41% in HIV-infected MSM and by 16% in the HIV-uninfected counterparts with a unit increase in the number of genotypes in the anal sample. Although these findings are consistent with those reported by others, 24,25,36,42 it is still unclear whether multiple infections have a role in the development of anal cancer and its precursors. Interestingly, a recent study 43 showed that multiple infections by HR types may increase the risk of HGAIN recurrence.…”
Section: Cancer Cytopathologysupporting
confidence: 92%
See 1 more Smart Citation
“…Our study also demonstrated that numbers of HPV genotypes (both oncogenic [OR = 1.35] and non-oncogenic [OR = 1.25], Table 2) were associated with increased risk of developing anal dysplasia. Previous reports have shown a strong association between number of HPV types and anal SILs [40]. HPV types 16 and/or 18 have been considered the most important genotypes found in anal cancer [22] and have been strongly associated with HGAINs in previous studies [13,17].…”
Section: Discussionmentioning
confidence: 90%
“…Associations between multiple oncogenic HPV infections and HGAINs have also been reported [13,17]. Briefly, persistent anal infection with multiple types of HPVs, including oncogenic HPVs, is one of the risk factors for the progression of high-grade anal intraepithelial neoplasms [40,42,43], and anal squamous intraepithelial neoplasms are known precursors of anal cancer [44][45][46]. Currently, HPV vaccines have been approved for young MSM for prevention of HGAIN in western countries [47], and this strategy could also be considered in other countries if resources are available.…”
Section: Discussionmentioning
confidence: 98%